Functional analysis and development of a CRISPR/Cas9 allelic series for a CPR5 ortholog necessary for proper growth of soybean trichomes - Campbell, Benjamin W. (Sci Rep, 2019)
Developments in genomic and genome editing technologies have facilitated the mapping, cloning, and validation of genetic variants underlying trait variation. This study combined bulked-segregant analysis, array comparative genomic hybridization, and CRISPR/Cas9 methodologies to identify a CPR5 ortholog essential for proper trichome growth in soybean (Glycine max). A fast neutron mutant line exhibited short trichomes with smaller trichome nuclei compared to its parent line. A fast neutron-induced deletion was identified within an interval on chromosome 6 that co-segregated with the trichome phenotype. The deletion encompassed six gene models including an ortholog of Arabidopsis thaliana CPR5. CRISPR/Cas9 was used to mutate the CPR5 ortholog, resulting in five plants harboring a total of four different putative knockout alleles and two in-frame alleles. Phenotypic analysis of the mutants validated the candidate gene, and included intermediate phenotypes that co-segregated with the in-frame alleles. These findings demonstrate that the CPR5 ortholog is essential for proper growth and development of soybean trichomes, similar to observations in A. thaliana. Furthermore, this work demonstrates the value of using CRISPR/Cas9 to generate an allelic series and intermediate phenotypes for functional analysis of candidate genes and/or the development of novel traits.